A study on the reliability and validity of the Korean version of the parenting outcome expectancy scale for parents of elementary school students - Kim, Yoonjung; Lee, Jungmin; Ross, Ratchneewan (Frontiers in Psychology, 2023)
Introduction Many parents do not engage in active discussions with their children about sexuality. This can contribute to negative sexual and reproductive health outcomes among youth. To foster a healthy environment for sexual activity, it is crucial for parents to provide comprehensive sex education to their children at home. This study aims to cross-culturally adapt and evaluate the psychometric properties of a Korean version of the Parenting Outcome Expectancy Scale to measure the sexual communication abilities of parents of elementary school students in South Korea. Method The study participants were parents of elementary school students between 6 to 13 years old. We used exploratory and confirmatory factor analyses to examine the reliability and validity of the 23-item Korean version of the Parenting Outcome Expectancy Scale. Results The study confirms the reliability and validity of the scale, comprising five factors and 22 items, for the evaluation of the outcome expectancy of communication about sex between parents and their children. Results also demonstrate that talking about sex is still a challenge for many parents. Discussion This instrument can help parents prepare for sex communication with their children and for sexual education, potentially yielding a positive effect on children’s sexual health and parental satisfaction.